IDENTIFIKASI KELEMBAGAAN LOKAL DALAM RANGKA IMPLEMENTASI DAERAH PERLINDUNGAN LAUT BERBASIS MASYARAKAT (DPL-BM) DI KOMUNITAS DESA SEKUNYIT KABUPATEN KAUR - Badrudin, Redy; Widiono, Septri (Jurnal AGRISEP, 2011)
This research is aimed to identify the local institutions as a basic for  DPL-BM implementation, located in Sekunyit  village,  Kaur Selatan sub-district, district of Kaur.  Qualitatif data obtained from Focus Group Discussion (FGD)  and Key persons who are resourceable dan knowlegeble in the term of local institutions. This research was done in February and December 2009. The results are (1) As a general the condition of Socio-Economics of Desa Sekunyit People doing the occupation Fishermen dan Farmers, especially  rainfed paddy, (2) Local institusion which is existing Farmer Group, coopperatives, Fishermen group, PKK, and religius group (pengajian), dan (3) DPL-BM institution founded is the modification of local institution. DPL-BM consisfs of DPL institution for men, Nafkah ganda group for women. (4) Rural goverment back up the DPl-BM through publishing the village rule about DPL-BM.